Decolonial considerations of environmentalism: Observations from a (US) State Park - Lies, Trevor S.; Adams, Glenn; Santangelo, Byron (PINS-Psychology in Society, 2022)
In this contribution to the special issue, we explore implications of decolonial theory for understanding climate change skepticism and environmental concern. The empirical portion of this project entailed interviews about perceptions of recent extreme weather, climate change, and environmental concern with N = 41 visitors to a Kansas (USA) state park, a population we selected for their (presumed) high environmental concern. Although most respondents reported personal experience of extreme weather, only a smaller subset believed these events reflected anthropogenic climate change (ACC). Consistent with other research, this tendency to be skeptical of climate change and its connection to extreme weather was greater among white participants than participants of color, a pattern we interpret as collectively motivated white ignorance about the role of modern/colonial violence in the production of the ecological crisis. Results also revealed an environmental concern characterized by wilderness preservation and individual action. We conclude by situating climate change perceptions and environmental concern within a decolonial perspective as an alternative foundation for environmentalism and psychology.